1971
DOI: 10.1002/jlac.19717490104
|View full text |Cite
|
Sign up to set email alerts
|

Synthese von Amidrazonen aus Amidinen

Abstract: Die aliphatischen Aniidine l a -e reagieren mit Hydrazin innerhalb von 5-10 Minuten in nahezu quantitativer Ausbeute zu den Amidrazonen 2a-e ; bei aromatischen Amidinen (If, g) betragt die Reaktionszeit etwa 4 Stunden, wobei 2f bzw. g entsteht. Die Amidrazone 2a-g werden entweder als Hydrochloride isoliert oder durch Reaktion mit den 1.2-DioxoVerbindungen 3a-f als 1.2.4-Triazine (4a-0) nachgewiesen. Synthesis of Amidrazones from AmidinesThe aliphatic amidines l a -e and hydrazine form the amidrazones 2a-e with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…3,5-Di- tert -butyl-2-hydroxybenzaldehyde S-methylisothiosemicarbazone was prepared by condensation reaction of equimolar amounts of 3,5-di- tert -butyl-2-hydroxybenzaldehyde and S-methylisothiosemicarbazide hydroiodide in EtOH/H 2 O 1:1 followed by addition of equivalent amount of Na 2 CO 3 . Acetamidrazone hydrochloride was prepared as described in the literature 24. Condensation reaction between 3,5-di- tert -butyl-2-hydroxybenzaldehyde and acetamidrazone hydrochloride in ethanol/water 2:1 in the presence of equimolar amount of Na 2 CO 3 afforded a Schiff base.…”
Section: Methodsmentioning
confidence: 99%
“…3,5-Di- tert -butyl-2-hydroxybenzaldehyde S-methylisothiosemicarbazone was prepared by condensation reaction of equimolar amounts of 3,5-di- tert -butyl-2-hydroxybenzaldehyde and S-methylisothiosemicarbazide hydroiodide in EtOH/H 2 O 1:1 followed by addition of equivalent amount of Na 2 CO 3 . Acetamidrazone hydrochloride was prepared as described in the literature 24. Condensation reaction between 3,5-di- tert -butyl-2-hydroxybenzaldehyde and acetamidrazone hydrochloride in ethanol/water 2:1 in the presence of equimolar amount of Na 2 CO 3 afforded a Schiff base.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction of hydroxyamidrazone 30 with dimethylglyoxal 31 in methanol affords 5,6-dimethyl-3-phenyl-1,2,4-triazine 4-oxide 32. 31 The condensation of amidrazone 33 with phenylglyoxal monooxime 34 occurs through the formation of hydrazone 35. The elimination of an ammonia molecule from compound 35 gives 3-methyl-6-phenyl-1,2,4-triazine 4-oxide 36 in a good yield.…”
Section: Methods For the Synthesis Of 124-triazine N-oxidesmentioning
confidence: 99%
“…the amidine hydrochlorides 3, can be difficult. [15] For this reason we employed a new strategy and compounds 4 were synthesized in a one-pot synthesis, without isolation of the intermediates (Scheme 1), using wellchosen reaction times as described in the Experimental section. Initially, it was confirmed that no by-products were formed in each step.…”
Section: Results and Discussion Synthesismentioning
confidence: 99%